Atrial chamber remodelling in healthy pre-adolescent athletes engaged in endurance sports: A study with a longitudinal design. The CHILD study. (15th November 2016) - D'Ascenzi, Flavio; Solari, Marco; Anselmi, Francesca; Maffei, Silvia; Focardi, Marta; Bonifazi, Marco; Mondillo, Sergio; Henein, Michael
Abstract: Aims: Previous studies investigated the exercise-induced adaptation of left (LA) and right atrium (RA) in adults, but little is known about respective changes in the growing heart of children. We aimed to longitudinally investigate the effects of endurance training on biatrial remodelling in preadolescent athletes. Methods and results: Ninety-four children (57 endurance athletes, 37 sedentary controls; mean age 10.8 ± 0.2 and 10.2 ± 0.2 years, respectively) were evaluated at baseline and after 5 months by ECG and by two-dimensional, three-dimensional (3D) and speckle-tracking echocardiography. Athletes were trained at least 10 h/week. The resting heart rate was lower in athletes ( p  = 0.046) and decreased further after training ( p  < 0.0001). Neither athletes nor controls had ECG evidence for LA or RA enlargement. At baseline, indexed LA volumes did not differ between groups ( p  = 0.14) but indexed RA dimensions were larger in athletes ( p  = 0.007). After 5 months, indexed LA volumes increased in athletes but not in controls ( p  < 0.0001, p  = 0.29; respectively) while indexed RA volumes increased in both groups (p < 0.0001, p  = 0.018; respectively). At the same time, slight differences in biatrial reservoir and contractile function were found either in athletes, as demonstrated by speckle-tracking echocardiography, but 3D-derived LA and RA ejection fraction remained stable in both groups. Conclusion: Endurance training influences the growing heart of preadolescent athletes with an additive increase in biatrial size, suggesting that morphological adaptations can occur also in the early phases of the sports career. Training-induced remodelling was associated with a preserved biatrial function, supporting the hypothesis of a physiological remodelling.